The determinants of profitability in Sharia-compliant corporations: evidence from Jordan. Issue 4 (8th July 2019) - Alsharari, Nizar Mohammad; Alhmoud, Turki Raji
Abstract : Purpose: The purpose of this paper is to examine the determinants of profitability of 28 Sharia -compliant corporations in Jordan over the three-year period of 2013-2015. Design/methodology/approach: The two-stage least square (2SLS) regression analysis with fixed effects was conducted using two measures of profitability, namely: return on assets and return on equity. The empirical data were collected from 28 Sharia -compliant corporations in Jordan over the study period. A variety of internal and external factors was used to determine profitability. Findings: In general, this analysis of the determinants of profitability for Sharia -compliant corporations confirmed previous findings. Regression findings revealed that previous year profitability, debt ratio, organizational structure, the size of the audit firm and voluntary disclosure to be important determinants of profitability of Sharia -compliant corporations in Jordan from 2013 to 2015. The independent variables of firm size, ownership ratio greater than 5%, liquidity ratio, percentage of non-Jordanian ownership or the age of the firm were not found to significantly influence the profitability of the corporations studied. Research limitations/implications: The authors determined that the independent variables selected, with few exceptions, behaved according to expectations. Moreover, the current literature on the influence of management on performance, and thus, profitability, does not consider the philosophy under which business is conducted (a limitation with respect to the type of business conducted). For example, Sharia -compliant and non- Sharia -compliant firms operate under different sets of principles and rules. This variance in business philosophies may have an important bearing on management style, an aspect that has been neglected in the organizational management literature. The panel data from a three-year period was insufficient to validate the consistency of the results; future researchers may increase the length of the study periods to confirm results and increase the robustness of the data collection method. Practical implications: The findings from the study have implications that may be functional for businesses, investors and policymakers in their focus on the Sharia -compliant business sector in Jordan. The factors influencing profitability may inform the setting of regulatory policy designed to stabilize and sustain the performance of Sharia -compliant corporations more broadly. Originality/value: This study contributes to the growing body of literature on Islamic finance, and can be considered one of a very few that have examined the internal and external determinants of the profitability of Sharia -compliant corporations in a developing country such as Jordan, using panel data.